PERUBAHAN POLITIK LUAR NEGERI RUSIA TERHADAP SURIAH DALAM KONFLIK INTERNAL SURIAH (2011 – 2017) - Fatmawati Fatmawati (LPPM Universitas Abdurrab, 2020)
Since the beginning of Syrian conflict in 2011, Russia as an important ally for Syria had supported the Assad’s government in order to defend Assad's regime. Russia acted as a direct supporter to Assad’s regime through non-military support, deploying economic assistance, and military support in the form of military cooperation. However, after the fall of the city of Aleppo, which represented a major coalition of forces supporting the regime since Russian military intervention in September 2015, Russia has changed its foreign policy in Syrian conflict. Russia hastened to hold a tripartite meeting in Moscow that involved Turkey and Iran to agree on the principles of peace in Syria which was known as Moskow Declaration. From military aspect, Russia reduced a large number of equipments and military forces in Syria. This research will discuss an overview form of Russia's foreign policy changes to Syria in the Syrian internal conflict between 2011 and 2017 through the concept of non-military support, military cooperation, mediation, negotiation, and peace making. This research applied qualitative research approach with descriptive research type and collected secondary data from various sources that have been published. The finding of this research showed that there was a pattern of form of Russia’s foreign policy changes from direct supporter of Assad’s regime to mediator in the Syrian internal conflict between 2011 and 2017. Keywords: Syrian Conflict, Foreign Policy, Direct Supporter, and Mediator.